2020
DOI: 10.3390/molecules25184327
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Solubilization of Phenanthrene by Mixed Micelles Composed of Biosurfactants and a Conventional Non-Ionic Surfactant

Abstract: This study investigated the solubilization capabilities of rhamnolipids biosurfactant and synthetic surfactant mixtures for the application of a mixed surfactant in surfactant-enhanced remediation. The mass ratios between Triton X-100 and rhamnolipids were set at 1:0, 9:1, 3:1, 1:1, 1:3, and 0:1. The ideal critical micelle concentration values of the Triton X-100/rhamnolipids mixture system were higher than that of the theoretical predicted value suggesting the existence of interactions between the two surfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 52 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In recent years, many studies have been carried out on the solubilization of PAHs by surfactants [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Aryal et al reported that a single surfactant solution above CMC can enhance the solubility of phenanthrene (Phe) and pyrene (Pyr) in water, and the solubility was linearly proportional to the surfactant concentration [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have been carried out on the solubilization of PAHs by surfactants [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Aryal et al reported that a single surfactant solution above CMC can enhance the solubility of phenanthrene (Phe) and pyrene (Pyr) in water, and the solubility was linearly proportional to the surfactant concentration [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compatibility is the basis of the application of surfactants, and the surface properties of ordinary hydrosiloxanes in aqueous solution are limited [34]. In order to improve the use of various surfactants, in the daily preparation of formulations, the form of compounding is often used to integrate various functions of surfactants into one system, so as to achieve a synergistic effect.…”
Section: Compatibility Of Mpntsmentioning
confidence: 99%
“…The characterization of rhamnolipid behavior in aqueous solutions and at the air/water interface also includes a few examples focusing on surfactant mixtures composed of rhamnolipids and other surfactants, either anionic or nonionic ones, namely, sodium dodecylbenzenesulfonate [ 176 , 199 ], sodium dodecylsulfate [ 224 ], sodium laurylethersulfate [ 225 ], lactonic sophorolipid [ 226 ], the aliphatic alcohol ethoxylate surfactant tergitol 15-S-7 [ 227 ], Triton X-100 [ 228 ], and Triton X-165 [ 229 ]. These studies highlight deviations from the ideal mixing pointing toward synergistic interactions between rhamnolipids and sophorolipid [ 226 ], sodium dodecylsulfate [ 224 ], and both Triton surfactants [ 228 , 229 ]. On the other hand, antagonistic interactions take place between rhamnolipids and sodium laurylethersulfate [ 225 ], while the scenario is more complex in the case of dodecylbenzenesulfonate, with an ideal behavior for mixtures containing R1 and deviations from ideality for mixture containing R2 or both R1 and R2 [ 176 ].…”
Section: Open Issuesmentioning
confidence: 99%